DFT Studies on Ni-Mediated C–F Cleavage for the Synthesis of Cyclopentadiene Derivatives - Chen, Wen-Jie; Xu, Ruo-Nan; Lin, Weimin; Sun, Xuejiao; Wang, Bin; Wu, Qi-Hui; Huang, Xin (Frontiers in Chemistry, 2018)
Density functional theory calculations have been performed to study the detailed mechanism of Ni-mediated [3+2] cycloaddition of 2-trifluoromethyl-1-alkenes with alkynes via cleavage of two C-F bonds. It was found that the reaction pathway involves oxidative addition, the first β-fluorine elimination, and then intramolecular 5-endo insertion of difluoroalkene, followed by the second cleavage of C-F bond, and finally the dissociation of difluorides yields the fluorine-containing product cyclopentadienes in sequence. The overall rate-determining step is the combined processes of the β-fluorine elimination and the 5-endo insertion. Furthermore, we investigated the regioselectivity of asymmetric alkynes. The detailed energy profiles and structures are presented in this study.